Measurement of t(t)over-bar production in the tau plus jets topology using p(p)over-bar collisions root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ripp-Baudot, I.; et al. (Amer Physical Soc, 2010)
We present a measurement of the t (t) over bar production cross section multiplied by the branching ratio to tau lepton decaying semihadronically (tau(h)) plus jets, sigma(p (p) over bar -> t (t) over bar + X) center dot BR(t (t) over bar -> tau(h) + jets), at a center of mass energy root s = 1.96 TeV using 1 fb(-1) of integrated luminosity collected with the D0 detector. Assuming a top quark mass of 170 GeV, we measure sigma(t (t) over bar) center dot BR(tau h) (+ j) = 0.60(-0.22)(+0.23)(stat)(-0.14)(+0.15)(syst) +/- 0.04(lumi) pb. In addition, we extract the t (t) over bar production cross section using the t (t) over bar -> tau(h) + jets topology, with the result sigma(t (t) over bar) = 6.9(-1.2)(+1.2)(stat)(-0.7)(+0.8)(syst) +/- 0.4(lumi) pb. These findings are in good agreement with standard model predictions and measurements performed using other top quark decay channels.